Air-sea fluxes of methanol, acetone, acetaldehyde, isoprene and DMS from a Norwegian fjord following a phytoplankton bloom in a mesocosm experiment - V. Sinha; J. Williams; M. Meyerhöfer; U. Riebesell; A. I. Paulino; A. Larsen (Atmospheric Chemistry and Physics, 2007)
The ocean's influence on volatile organic compounds (VOCs) in the atmosphere is poorly understood. This work characterises the oceanic emission and/or uptake of methanol, acetone, acetaldehyde, isoprene and dimethyl sulphide (DMS) as a function of photosynthetically active radiation (PAR) and a suite of biological parameters. The measurements were taken following a phytoplankton bloom, in May/June 2005 with a proton transfer reaction mass spectrometer (PTR-MS), from mesocosm enclosures anchored in the Raunefjord, Southern Norway. The net flux of methanol was always into the ocean, and was stronger at night. Isoprene and acetaldehyde were emitted from the ocean, correlating with light (ravcorr, isoprene=0.49; ravcorr, acetaldehyde=0.70) and phytoplankton abundance. DMS was also emitted to the air but did not correlate significantly with light (ravcorr, dms=0.01). Under conditions of high biological activity and a PAR of ~450 μmol photons m−2 s−1, acetone was emitted from the ocean, otherwise it was uptaken. The inter-VOC correlations were highest between the day time emission fluxes of acetone and acetaldehyde (rav=0.96), acetaldehyde and isoprene (rav=0.88) and acetone and isoprene (rav=0.85). The mean fluxes for methanol, acetone, acetaldehyde, isoprene and DMS were −0.26 ng m−2 s−1, 0.21 ng m−2 s−1, 0.23 ng m−2 s−1, 0.12 ng m−2 s−1 and 0.3 ng m−2 s−1, respectively. This work shows that compound specific PAR and biological dependency should be used for estimating the influence of the global ocean on atmospheric VOC budgets.